Physical Properties of Macroporous Tungsten Oxide Thin Films and Their Impact on the Photocurrent Density - I. Riech; M. Acosta; M. A. Zambrano-Arjona; F. Peñuñuri; M. Rosado-Mendoza; E. Marín; P. Rodríguez-Fragoso; J. G. Mendoza-Álvarez (International Journal of Photoenergy)
Tungsten trioxide (WO3) films were prepared using polystyrene spheres of two different diameters as a template in order to create porous layers. X-ray diffraction data and electron microscopy images show that annealed films exhibit polycrystalline structure with monoclinic phase and pore size of approximately hundred nanometers. The optical band gap energies have been determined by photoacoustic spectroscopy as 3.17 eV, and this value was not affected by sample morphology. Low temperature photoluminescence spectra exhibit broad band in the blue region. Deconvolutions of PL spectra show that there are two transitions which intensity depends on thin film pore size. We discuss the possible origin of this emissions associated with oxygen vacancies and surface states. A comparative study of the WO3 films used as photoanodes is presented and correlated with PL results.